Toxins and drug discovery - Cruz, Lourdes J.; Luo, Sulan; Gopalakrishnakone, P. (Springer, 2017)
This volume deals mainly with the specialized aspect of toxins and drug discovery. Man has been using natural resources especially plants to treat diseases from very early times in history of mankind. Although many drugs derived from plants and microbes have been discovered and being used in clinical practice, not many drugs have been developed from venoms and toxins although many laboratories worldwide are actively working on it. This volume describe some of the recent developments in this research area, such as snake venoms, conotoxins, bioinformatics in drug discovery from peptide toxins.
Includes index.
Keywords: Toxins.; Drug development.; elektronické knihy; electronic books